Unveiling the link between facets of positive nonverbal communication and perceived leader effectiveness: A moderated mediation model. Issue 4 (7th August 2016) - Bellou, Victoria; Gkorezis, Panagiotis
ABSTRACT: Previous experimental research has examined the important role of combined facets of kinesics and paralanguage in engendering perceived leader effectiveness. However, little is known about the distinct impact of these overarching forms of nonverbal communication and the underlying mechanisms that account for this relationship. Hence, conducting a scenario and a survey, we examined the affect of leader positive kinesics and paralanguage on perceived leader effectiveness through trust in leader. Furthermore, we investigated if these indirect effects are contingent on a novel personality trait--namely, suspicion. The present results demonstrated that suspicion moderated the mediating effect of trust in leader on the relationship between both kinesics and paralanguage and perceived leader effectiveness. Implications and future research are also discussed.